Manching, Deutschland: Abschluss der Arbeiten und Publikation - Sievers, Susanne (e-Forschungsberichte des DAI, 2023)
The oppidum of Manching, Lkr. Pfaffenhofen/Ilm, has been the only longterm project of the Romano-Germanic Commission at Frankfurt/Main since 1955/56. During this time, a large area of 30 ha has been excavated (Abb. 1) which has yielded valuable information on Celtic urbanization and society. With 380 ha of unevenly settled interior, surrounded by a massive wall, Manching is one of the largest oppida in Europe. The earliest traces of later Iron Age occupation belong to the late 4th century, the latest belong to the mid- 1st century BC. During the last years two PhD theses could present new results, one of them concerning the environment of Manching, the other analyzing the function of the southern periphery of the oppidum and the role of ditch systems.